2008
DOI: 10.1136/emj.2007.054361
|View full text |Cite
|
Sign up to set email alerts
|

Risk management during inter-hospital transfer of critically ill patients: making the journey safe

Abstract: The Health and Safety Act requires from all employers the absolute necessity to perform risk assessments and to provide a safe environment in the workplace including provision of all necessary protective attire and equipment. NHS hospitals are clearly falling short of these legal requirements and are also in breach of national guidelines governing the issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The guidelines described by SCCM for interfacility patient transfers focuses on services that exceed the available resources of the transferring facility [17,19,20]. They describe trying to stabilize the patient prior to transfer but also acknowledge that the patient may not be able to be fully stabilized until they have reached the receiving hospital [5,21]. Brunsveld-Reinder et al developed a checklist for intra hospital transport safety.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The guidelines described by SCCM for interfacility patient transfers focuses on services that exceed the available resources of the transferring facility [17,19,20]. They describe trying to stabilize the patient prior to transfer but also acknowledge that the patient may not be able to be fully stabilized until they have reached the receiving hospital [5,21]. Brunsveld-Reinder et al developed a checklist for intra hospital transport safety.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…It is known that any transport of critically patients puts them at increased risk of significant morbidity and mortality. Adverse events have been cited at anywhere from 30-70%, and the physiologic changes can be life threatening particularly in ventilator-dependent patients [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Si el equipamiento no se encuentra adecuadamente posicionado y fijo, en caso de una desaceleración brusca, estos se pueden desplazar, convirtiéndose en verdaderos proyectiles que pueden impactar al paciente o al equipo de traslado. La velocidad de traslado, por lo tanto, debe ser de preferencia continua y estable, que permita maniobras de reanimación en caso de requerirlas y siempre tener en cuenta la seguridad del equipo de traslado y del paciente (9) . Cabe mencionar que durante el traslado se pueden realizar maniobras de reanimación; no obstante, la calidad de estas es discutible.…”
Section: Riesgos Durante El Trasladounclassified
“…6 A survey of risk management strategies practised by NHS hospitals when transferring critically ill patients concluded that many NHS hospitals fall short of national guidelines. 7 This problem is however not just confined to the NHS. In an audit of transfers to Cork University Hospital in Ireland, only 22% of patients were accompanied by a doctor, 8 while an audit from the University Hospital in Lausanne, Switzerland, showed that compliance with local transfer guidelines was below 100%, with particular concerns about resourcing at weekends.…”
Section: Improving the Quality Of Transfersmentioning
confidence: 99%